PENGARUH EFEKTIFITAS SHADING TERHADAP KENYAMANAN TERMAL : STUDI KASUS: MASJID ISTIQLAL JAKARTA PUSAT - Fita Wulandari; Marchiano Sabastiano; Doddy Anwar (NALARs, 2026)
The building envelope acting as shading plays a vital role in tropical architectural design, especially in achieving thermal comfort. This research aims to assess the effectiveness of shading elements in maintaining indoor thermal comfort at Istiqlal Mosque, Jakarta. The applied method was quantitative-descriptive through direct measurements of temperature, humidity, and light intensity, combined with user questionnaires. The mosque’s double-skin façade, made of stainlesssteel sheets, functions to reduce solar heat gain and lower indoor temperature. Structural columns also act as additional shading components. Results show that shading effectively reduces solar radiation, stabilizes room temperature, and enhances user comfort. Beyond its functional role, the shading also enriches the building’s aesthetic expression. Therefore, shading elements prove to be both thermally and visually efficient in supporting tropical architectural design.